El colegio de infantes en Morelia 1878-1914 - Zuno Rodiles, Edgar (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
For centuries the Catholic church has had control of the conscience of the majority of the population, a situation that will not be until the nineteenth century when there is a rupture with the state, slowing the ecclesiastical power, despite that, Catholic education continued Its work, gaining more force especially in the last decades of the mentioned century. The first Colegio de Infantes that we find, had its origin in 1695 in Puebla, later the one of the city of Mexico appears in the year of 1734 by agreement of the ecclesiastical authorities of the cathedral capitalina; The goal was to prepare the infants to be part of the choir of this institution. For their entry they had to meet certain requirements such as: being between seven and nine years of age, good voice, being children of poor Spaniards, the taste for music, being good-looking and most important, discipline to lead a life as if they were Seminarians where apart from singing and music they would receive instruction in which subjects such as grammar and theology would be taught. The teaching method that was applied to the infants according to the characteristics of this one was the traditional one, where the teacher was the only one who spoke in the class, which was maintained until the closing of the Institution.

Durante siglos la iglesia católica ha tenido el control de la conciencia de la mayoría de la población, situación que no será sino hasta el siglo XIX cuando se da una ruptura con el Estado, frenando el poderío eclesiástico, pese a ello, la educación católica continuaba su labor, cobrando mayor fuerza sobre todo en las últimas décadas del mencionado siglo. El primer Colegio de Infantes que encontramos, tuvo su origen en 1695 en Puebla, posteriormente surge el de la ciudad de México en el año de 1734 por acuerdo de las autoridades eclesiásticas de la catedral capitalina; el objetivo era preparar a los infantes para formar parte del coro de dicha institución. Para su ingreso debían cumplir con ciertos requisitos como: tener entre siete y nueve años de edad, buena voz, ser hijos de españoles pobres, el gusto por la música, ser bien parecidos y lo más importante, disciplina para llevar una vida como si fueran seminaristas en donde aparte del canto y la música recibirían instrucción en la que se impartirían materias como gramática y teología. El método de enseñanza que se aplicó a los infantes de acuerdo a las características de éste fue el tradicional, donde el maestro era el único que hablaba en la clase, mismo que se mantuvo hasta el cierre de la Institución.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2008-0017; Educación; Educación católica; México; Infantería; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/247